Lviv petit-bourgeois humor on the example of the magazines “Goniec i Iskra” and “Wesoły Kurierek” - Fałat, Piotr (Laughter, humour, satire, 2024)
“Wesoły Kurjerek” is a humorous supplement to the magazine “Goniec i Iskry”, which was arranged in Lviv from July 1, 1893 to August 1899. on: “Happy Kurjerek Illustrowany” or “Happy Kurjerek for All”. The petty-bourgeois joke of “Wesoły Kurjerek” was presented in the form of humorous dialogues, poems or charades. They concerned love, family and economic and living matters. The aim of the article is to recreate the issues that were laughed at in Lviv at the end of the 19th century. Examination of the detailed subject of jokes in “Wesoły Kurierek” will indicate the areas which were interesting for its recipients. The typographic and graphic aspect of the journal will also be analyzed in order to check to what extent these elements served to emphasize the humorous nature of the published content. The study fills the research gap in the field of 19th-century Lviv satirical and humorous magazines and opens the field for further discussion.